Evaluation of the multiplex PCR based assay Unyvero implant and tissue infection application for pathogen and antibiotic resistance gene detection in children and neonates - Papan, Cihan; Meyer-Buehn, Melanie; Laniado, Gudrun; Hübner, Johannes (Infection, 2019)
BackgroundSkin and soft tissue infections have a high disease burden in children. The emergence of multidrug-resistant bacteria over the last decades has heavily influenced hospitalization rates, morbidity and mortality. In addition, with increased survival rates in neonatology and oncology, health-care associated infections are more frequently encountered. There is a growing need for fast and feasible diagnostic tools for the recognition of microorganisms and drug resistances.MethodsIn this prospective study, we compared results of routine culture with the multiplex PCR based Unyvero Implant and Tissue Infection (ITI) application. Specimens were obtained from different sources from neonates and children.ResultsWe analyzed specimens from 29 patients (72.4% male) with a median age of 8.1 years (range 0.03-15.2). Concordance between Unyvero ITI and culture was reached in 16 of 29 samples (55.2%). Unyvero ITI yielded an overall sensitivity and specificity of 76.3% and 96.5%, respectively. Accuracies were best for non-fermenting bacteria, for which sensitivity was 100% and specificity 98.2%. Detection rates were lower for Gram-positive bacteria (68.8 and 95.2%, respectively). Unyvero correctly detected one blaOXA−24/40 producing Acinetobacter baumannii, while none of the six gyrA87 had a correlate in antimicrobial susceptibility testing.ConclusionsUnyvero ITI quickly provides additional information relevant for clinical decision-makers. Sensitivity of the PCR must be improved especially for Gram-positive bacteria, and further studies are needed to assess the impact on clinical decision-making and outcome.
First online: 21 August 2018
Gesehen am 19.08.2019